2011
DOI: 10.1016/j.mrfmmm.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental chemicals and microRNAs

Abstract: MicroRNAs (miRNAs) are short single-stranded non-coding molecules that function as negative regulators to silence or suppress gene expression. Aberrant miRNA expression has been implicated in a several cellular processes and pathogenic pathways of a number of diseases. Evidence is rapidly growing that miRNA regulation of gene expression may be affected by environmental chemicals. These environmental exposures include those that have frequently been associated with chronic diseases, such as heavy metals, air po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(97 citation statements)
references
References 86 publications
(76 reference statements)
2
95
0
Order By: Relevance
“…For instance, the technical procedure should be standardized in terms of sample storage, collection and transportation, as well as miRNA extraction, detection, normalization, reproducibility, validation and analysis (123,124). The identification of miRNA targets is another limitation that has to be overcome to elucidate the biological function of specific miRNAs (124). According to their mechanisms of action, each miRNA may present incomplete complementarity with several target mRNAs and therefore regulate the expression of numerous transcripts and vice versa, as one mRNA can be modulated by many miRNAs.…”
Section: Somatic Cell Mutationsmentioning
confidence: 99%
“…For instance, the technical procedure should be standardized in terms of sample storage, collection and transportation, as well as miRNA extraction, detection, normalization, reproducibility, validation and analysis (123,124). The identification of miRNA targets is another limitation that has to be overcome to elucidate the biological function of specific miRNAs (124). According to their mechanisms of action, each miRNA may present incomplete complementarity with several target mRNAs and therefore regulate the expression of numerous transcripts and vice versa, as one mRNA can be modulated by many miRNAs.…”
Section: Somatic Cell Mutationsmentioning
confidence: 99%
“…References selected from PubMed search (pregnancy or in utero) and (exposome or multiple pollutant) to represent state of the science Studies were identified through the Pubmed search described above and from recent reviews [4,45,46] (including citing and cited references). Most studies have looked at single exposures that can be well measured during pregnancy to identify associated internal exposome profiles and improve mechanistic understanding (Table 2).…”
Section: Internal Pregnancy Exposome Studiesmentioning
confidence: 99%
“…Rager et al [39•] performed a similar analysis in a Mexican birth cohort; however, they also measured levels of miRNAs, small non-coding RNAs involved in regulation of messenger RNA (mRNA) translation. They identified 12 References selected from PubMed search (see Table 1) and recent reviews [4,45,46] (including citing and cited references) to represent state of the science miRNAs associated with arsenic exposure, many of which were known to have roles in carcinogenesis, and 334 mRNA transcripts including 28 identified in the study of Fry et al [38]. They found that a third of miRNA-mRNA pairings, predicted computationally based on target sequences, were correlated in their analysis.…”
Section: Internal Pregnancy Exposome Studiesmentioning
confidence: 99%
“…Over the past decade, there has been growing appreciation for the role that small regulatory RNAs, namely microRNAs (miRNAs), are playing in the maintenance of cellular homeostasis, disease progression and responsiveness to environmental stimuli including diet, smoking and response to physical activity (Dykxhoorn, 2010;Hou et al, 2011;Izzotti et al, 2011;Timmons, 2011). miRNAs exert their effect by recognizing specific target mRNA sequences and inducing translational silencing and/or mRNA degradation (Bartel, 2009).…”
Section: In Silico Mirna Target Predictionmentioning
confidence: 99%